STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN PADA SISWA DI SDN NO 14 TRANS SABUNG TAHUN AJARAN 2022 – 2023 - Ika Fitriana; Susilawati; Sera Yuliantini (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The purpose of this study is to discuss about: (1) Principal's Strategy in Improving Discipline in Students at SDN NO 14 Trans Sabung for the 2022-2023 Academic Year, Solutions Taken by the Principal in Overcoming Obstacles in Disciplining Students at SDN NO 14 Trans Sabung for the 2022-2023 Academic Year. This research uses a qualitative approach with a phenomenological type. The data collection techniques used are observation, interviews, and documentation. Meanwhile, data analysis is carried out through the stages of data collection, data reduction, data presentation, and conclusion drawn. Then the data validity check technique used is source triangulation and member check. The results of the study show that: 1. Strategies carried out by the principal in improving student discipline. planning a student discipline strategy.strategic planning is a process carried out by an organization to determine the strategy used or direction